Layered Double Hydroxide Sorbents for Removal of Selenium from Power Plant Wastewaters - Man Li; Tanzil Chowdhury; Andrea N. Kraetz; Hangkun Jing; Andrew Dopilka; Lisa M. Farmen; Shahnawaz Sinha; Candace K. Chan (ChemEngineering, 2019)
Selenium is an essential trace element but is increasingly becoming a contaminant of concern in the electric power industry due to the challenges of removing solubilized selenate anions, particularly in the presence of sulfate. In this work, we evaluate granulated layered double hydroxide (LDH) materials as sorbents for selenium removal from wastewaters obtained from a natural gas power plant with the aim to elucidate the effect of competing ions on the sorption capacities for selenium removal. We first present jar test data, followed by small-scale column testing in 0.43 inch (1.1 cm) and 2 inch (5.08 cm) diameter testbed columns for the treatment of as-obtained cooling tower blowdown waters and plant wastewaters. Finally, we present field results from a pilot-scale study evaluating the LDH media for treatment of cooling tower blowdown water. We find that despite the high levels of total dissolved solids and competing sulfate ions, the selenium oxoanions and other regulated metals such as chromium and arsenic are successfully removed using LDH media without needing any pre-treatment or pH adjustment of the wastewater.